2021
DOI: 10.1016/j.acra.2020.11.004
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Feature of COVID-19 Infection in Chest CT; “Pulmonary Target” Appearance

Abstract: Dear Editor-The novel Corona virus, COVID-19, which originated in Wuhan, China in December 2019, briefly called COVID-19, has become a pandemic disease. Although pulmonary manifestations predominate, other organs may be involved. The diagnosis is suspected on the clinical and radiologic findings and confirmed with RT-PCR tests. Findings of covid-19 on chest computed tomography (CT) are bilateral peripheral multifocal ground-glass opacities and patchy consolidations, linear opacities, reversed halo, and Crazy-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…3); außerdem finden sich Halo-und umgekehrtes Halo-Zeichen ("reversed halo" -Milchglas umgeben von ringförmiger Konsolidierung) sowie eine dezente Erweiterung der Gefäße in den betroffenen Lungenarealen [11][12][13]19]. Vereinzelt wurden auch das "ring of fire sign" (periphere ringförmige Verschattung, bestehend aus Konsolidierung und Milchglas, um normal transparentes Lungenparenchym) und das "target sign" (ringförmige Konsolidierung um regelrecht transparentes Lungenparenchym mit zentraler punktförmiger Verschattung, an eine Schießscheibe erinnernd) als spezifische bildgebende Befunde beschrieben [20][21][22].…”
Section: Covid-19-pneumonie Im Ctunclassified
See 1 more Smart Citation
“…3); außerdem finden sich Halo-und umgekehrtes Halo-Zeichen ("reversed halo" -Milchglas umgeben von ringförmiger Konsolidierung) sowie eine dezente Erweiterung der Gefäße in den betroffenen Lungenarealen [11][12][13]19]. Vereinzelt wurden auch das "ring of fire sign" (periphere ringförmige Verschattung, bestehend aus Konsolidierung und Milchglas, um normal transparentes Lungenparenchym) und das "target sign" (ringförmige Konsolidierung um regelrecht transparentes Lungenparenchym mit zentraler punktförmiger Verschattung, an eine Schießscheibe erinnernd) als spezifische bildgebende Befunde beschrieben [20][21][22].…”
Section: Covid-19-pneumonie Im Ctunclassified
“…Moreover, the halo sign and the reversed halo sign (ground glass opacity surrounded by a ring-shaped consolidation) as well as slight dilatation of the vessels in the affected lung areas have been reported 11 12 13 19 . In rare cases, the “ring of fire sign” (peripheral ring-shaped opacification consisting of consolidation and ground-glass opacity surrounding lung parenchyma with normal transparency) and the “target sign” (ring-shaped opacity around lung parenchyma with normal transparency containing a central hyperdensity reminiscent of a target) have been described as specific imaging findings 20 21 22 .…”
Section: Pulmonary Manifestationsmentioning
confidence: 99%
“…Subsequently, de Farias et al [ 14 ] and Müller et al [ 15 ] also reported this imaging feature and its variants. Recently, Jafari et al [ 16 ] reported four cases of “PTS”. In this contribution, we review chest CT images of 32 cases of PTS.…”
Section: Introductionmentioning
confidence: 99%
“…In reply to a letter to the editor entitled “Another Cause of the CT Target Sign: Influenza A (H1N1) Pneumonia” which is based on our previous article about Pulmonary Target Sign (PTS) in COVID19 ( 1 ), we would like to mention a few points that seem useful…”
mentioning
confidence: 99%